(untitled) (Panacea Journal of Medical Sciences, 2018)
Echinococcosis is caused primarily by one of two species of cestodes. Echinococcus granulosus and Echinococcus multilocularis. Here we present a case history of 18-year-old non-smoker farmer presented to the OPD with a one month history of moderate grade fever, 8 days history of cough with expectoration and a chest x-ray and CT thorax report suggestive of left upper lobe lung abscess. On routine bronchoscopy, the left upper lobe was seen completely obstructed with folded handkerchief shaped white membranous tissue which aroused the suspicion of a ruptured hydatid cyst. On review of the CT report, the lesion was reported to be a ruptured hydatid cyst and managed accordingly.